2008
DOI: 10.1073/pnas.0804461105
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to RevM10 inhibition reflects a conformational switch in the HIV-1 Rev response element

Abstract: Nuclear export of certain HIV-1 mRNAs requires an interaction between the viral Rev protein and the Rev response element (RRE), a structured element located in the Env region of its RNA genome. This interaction is an attractive target for both drug design and gene therapy, exemplified by RevM10, a transdominant negative protein that, when introduced into host cells, disrupts viral mRNA export. However, two silent G->A mutations in the RRE (RRE61) confer RevM10 resistance, which prompted us to examine RRE struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 38 publications
6
81
0
Order By: Relevance
“…Although the mechanism of resistance mediated by single nucleotide changes remains somewhat mysterious, our recent studies have unexpectedly shown that the changes cause a rearrangement of stem loops III, IV and V of the RRE into an alternative stable secondary structure that is more similar to the 5 stem-loop structure than the 4 stem-loop structure (137). Together these studies again highlight the point that regions in the RRE outside of the primary Rev binding site are important for Rev function.…”
Section: The Structure Of the Hiv-1 Rresupporting
confidence: 50%
See 4 more Smart Citations
“…Although the mechanism of resistance mediated by single nucleotide changes remains somewhat mysterious, our recent studies have unexpectedly shown that the changes cause a rearrangement of stem loops III, IV and V of the RRE into an alternative stable secondary structure that is more similar to the 5 stem-loop structure than the 4 stem-loop structure (137). Together these studies again highlight the point that regions in the RRE outside of the primary Rev binding site are important for Rev function.…”
Section: The Structure Of the Hiv-1 Rresupporting
confidence: 50%
“…Interestingly, the secondary structure determination of an in-vitro transcribed and folded 232-nt short NL4-3 RRE by the same SHAPE technology gave a different result (137). This study reported that the RRE forms an alternative 4 stem-loop structure, which structurally differs from the 5 stem-loop structure only in the rearrangement of stem-loops III and IV ( Figure 5B).…”
Section: The Structure Of the Hiv-1 Rrementioning
confidence: 87%
See 3 more Smart Citations